Dry electrode membrane and preparation method thereof, dry electrode and battery

By using a combination of PTFE and a low melting point second binder in the dry electrode film, the problem of insufficient tensile strength and peel strength of the existing dry electrode film is solved, and the improvement of high strength, flexibility and electrochemical performance is achieved, and it is especially suitable for small-particle size active material systems.

CN119275231BActive Publication Date: 2025-03-04ENPOWER (PEKING) INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411783063.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

During the preparation process of the existing dry electrode film, the tensile strength and the peel strength from the current collector are insufficient. Especially when a small particle size active material is active, the membrane is hard and brittle, difficult to form a film, and there is a problem of poor electrochemical stability.

Method used

The surface energy and bonding properties of the electrode material are improved through the mechanical mixing and hot pressing compounding process using a bonding combination including polytetrafluoroethylene (PTFE) as the first binder and a second binder with a melting point below 120°C.

Benefits of technology

The tensile strength and flexibility of the dry electrode film are improved, the adhesion to the current collector is enhanced, the cycle stability and electrochemical performance of the battery are improved, especially in the small particle size active material system, which significantly improves the energy density and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275231B_ABST
    Figure CN119275231B_ABST
Patent Text Reader

Abstract

The present invention provides a dry electrode film and a preparation method thereof, a dry electrode and a battery, and specifically relates to the technical field of secondary batteries. The dry electrode film includes an active material, a conductive agent and a binder; the binder includes a first binder and a second binder; the first binder is polytetrafluoroethylene; the melting point of the second binder is less than 120°C. The introduction of the second binder during the mixing process of the electrode material, the heat energy generated by the mechanical mixing can soften the second binder, bond the small particles together, improve the surface energy of the electrode material, drive the agglomeration or mixing behavior of the electrode particles during the dry mixing process, and form a high-strength dry film with high adhesion to the current collector; on the other hand, the second binder can soften at a lower temperature during the hot pressing composite current collector process, and is more tightly composited with the current collector, which optimizes the peeling strength between the electrode film and the current collector, and improves the cycle stability and electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a dry electrode film and a preparation method thereof, a dry electrode and a battery. Background Art

[0002] At present, the dry process has attracted more and more attention from the industry due to its advantages of low cost, high load and environmental friendliness. Especially in the field of solid-state batteries, dry electrodes can perfectly adapt to the sulfide system and avoid the influence of solvents on the electrolyte. However, when preparing dry membranes, only polytetrafluoroethylene (PTFE) is used. The tensile strength of the electrode membrane and the peeling strength between the electrode membrane and the current collector are still insufficient. Especially when the particle size of the active material is less than 5μm, the membrane prepared by PTFE alone is hard and brittle, has no flexibility, and even cannot form a membrane; in addition, the lowest unoccupied molecular orbital (LUMO) of PTFE is low, and it is easy to accept electrons, resulting in poor electrochemical stability and possible side reactions at low voltages.

[0003] Since small-particle active materials have more active sites and higher surface areas, they usually show higher reactivity. Therefore, in order to obtain better electrochemical performance, the particle size of the active material is generally set to be smaller. However, materials with small particle sizes have large specific surface areas, and it is difficult for the dry system of pure PTFE system to form a film continuously. Even if the film is formed, the film is hard and brittle, has no flexibility, and is easy to crack, making it impossible to carry out the subsequent solid-state battery assembly steps; in addition, the composite of the electrode film and the current collector is very important, but the pure PTFE system dry film has the problem of insufficient adhesion when composited with the current collector, which is easy to cause poor contact between the active dry film and the current collector during the battery cycle, thereby affecting the electrochemical performance of the battery.

[0004] In the existing technology for the preparation and optimization of dry membranes, in addition to improvements in process equipment, there are also many uses of composite binders, such as adding silicone resin adhesives to improve the adhesion between dry membranes and current collectors, or adding PVP to inhibit the reaction between PTFE and lithium. However, the existing solutions only optimize the system that has formed a membrane, and do not optimize the material system with small particle size and high specific surface area.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the objectives of the present invention is to provide a dry electrode membrane, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0007] A second object of the present invention is to provide a method for preparing a dry electrode membrane.

[0008] A third object of the present invention is to provide a dry electrode.

[0009] A fourth object of the present invention is to provide a battery.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A first aspect of the present invention provides a dry electrode membrane, comprising an active material, a conductive agent and a binder;

[0012] The adhesive comprises a first adhesive and a second adhesive;

[0013] The first binder is polytetrafluoroethylene or a copolymer of tetrafluoroethylene and a monomer;

[0014] The melting point of the second binder is less than 120°C.

[0015] Furthermore, the second binder includes at least one of PEG, PEO, amorphous PVDF, PMMA and polyvinyl chloride.

[0016] Furthermore, the mass ratio of the first binder to the second binder is 1:0.1-5.

[0017] Furthermore, the dry electrode membrane comprises, by weight, 30 to 95 parts of active material, 0 to 60 parts of solid electrolyte, 0.5 to 10 parts of conductive agent and 0.5 to 5 parts of binder.

[0018] The conductive agent includes at least one of VGCF, carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and graphene.

[0019] Furthermore, the active material includes a positive electrode active material and a negative electrode active material.

[0020] The positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel manganese cobalt oxide.

[0021] The negative electrode active material includes carbon material, silicon material, silicon-carbon composite material, lithium titanate or alloy material.

[0022] Furthermore, the active material is a positive electrode active material.

[0023] The dry-process positive electrode film comprises, by weight, 30 to 95 parts of positive electrode active material, 4 to 60 parts of solid electrolyte, 0.5 to 5 parts of conductive agent and 0.5 to 5 parts of binder.

[0024] The solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte and a composite electrolyte.

[0025] The second aspect of the present invention provides a method for preparing the dry electrode membrane, wherein the active material, the conductive agent and the binder are evenly mixed at a mixing speed of 300rpm-20000rpm and a mixing time of 0.1h-5h, followed by fiberization and finally a film formation using a roller press to obtain the dry electrode membrane.

[0026] Furthermore, the mixing temperature is less than 19°C.

[0027] The fiberizing is performed using high speed high shear equipment.

[0028] The high speed high shearing device includes at least one of a jet mill, a twin screw extruder, a mixer and a differential speed roller press. The third aspect of the present invention provides a dry electrode, including a current collector and a dry electrode film disposed on at least one side of the current collector.

[0029] A fourth aspect of the present invention provides a battery, comprising the dry electrode described in the third aspect.

[0030] Compared with the prior art, the present invention has at least the following beneficial effects:

[0031] In the dry electrode film provided by the present invention, the binder consists of a first binder and a second binder with a melting point lower than 120°C. The second binder is introduced during the mixing process of the electrode material. The heat energy generated by the mechanical mixing can soften the second binder, bond small particles together, improve the surface energy of the electrode material, drive the agglomeration or mixing behavior of the electrode particles during the dry mixing process, and form a dry film with high strength and high adhesion to the current collector. On the other hand, the second binder can soften at a lower temperature during the hot pressing composite current collector process, and composite more tightly with the current collector, thereby optimizing the peeling strength between the electrode film and the current collector and improving the cycle stability and electrochemical performance of the battery.

[0032] Such a binder composition not only enhances the tensile strength and flexibility of the electrode film, especially for active materials with a particle size of less than 5 microns, but also improves the electrochemical properties of the dry electrode, thereby improving the energy density and cycle stability of the battery, and also enhances the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a photo of the dry-process negative electrode film obtained in Comparative Example 2;

[0035] Figure 2 This is a photograph of the dry-process negative electrode film obtained in Example 9. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0037] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.

[0038] A first aspect of the present invention provides a dry electrode membrane, comprising an active material, a conductive agent and a binder;

[0039] The adhesive comprises a first adhesive and a second adhesive;

[0040] The first binder is polytetrafluoroethylene;

[0041] The melting point of the second binder is less than 120°C.

[0042] In the dry electrode film provided by the present invention, the binder consists of a first binder and a second binder with a melting point lower than 120°C. The second binder is introduced during the mixing process of the electrode material. The heat energy generated by the mechanical mixing can soften the second binder, bond small particles together, improve the surface energy of the electrode material, drive the agglomeration or mixing behavior of the electrode particles during the dry mixing process, and form a dry film with high strength and high adhesion to the current collector. On the other hand, the second binder can soften at a lower temperature during the hot pressing composite current collector process, and composite more tightly with the current collector, thereby optimizing the peeling strength between the electrode film and the current collector and improving the cycle stability and electrochemical performance of the battery.

[0043] Such a binder composition not only enhances the tensile strength and flexibility of the electrode film, especially for active materials with a particle size of less than 5 microns, but also improves the electrochemical properties of the dry electrode, thereby improving the energy density and cycle stability of the battery, and also enhances the safety of the battery.

[0044] As the first binder of dry electrode membrane, polytetrafluoroethylene (PTFE) has the advantage of significantly improving the performance and production efficiency of batteries. PTFE has excellent mechanical properties, high crystallinity, and the ability to fiberize, which makes it play an important role in the dry process. PTFE's flexibility, low resilience, medium tensile strength and high elongation at break fully meet the processing requirements of the electrode stretching process. PTFE powder microparticles can extend to form filamentous fibers when a shear load is applied. This fiberization process helps to form a stable electrode structure.

[0045] As the first binder, PTFE also helps to increase the proportion of active materials in the electrode and the thickness of the electrode layer, thereby significantly improving the energy density of the battery. In addition, the fiberization ability of PTFE allows the electrode membrane to be self-supporting, omitting the drying and recovery steps of the solvent, greatly reducing the cost of electrode manufacturing, and having environmentally friendly characteristics. The high chemical stability and electrical insulation of PTFE also help to improve the safety and cycle stability of the battery.

[0046] In terms of battery performance, the application of PTFE binder can enhance the capillary adsorption of liquid electrolytes by electrodes, bring good electrode flexibility and structural stability under compression, and thus significantly improve the electrochemical mechanical properties of electrodes. These characteristics combined make PTFE an ideal binder choice in dry electrode membranes, which helps promote the development of high-performance lithium-ion battery manufacturing technology.

[0047] Therefore, the present invention is directed to further improving the PTFE binder.

[0048] The second binder plays several key roles in the preparation of dry electrode membranes:

[0049] Improve the surface energy of electrode materials: During the mixing process of electrode materials, the heat energy generated by mechanical mixing can soften the second binder, thereby bonding small particles together and improving the surface energy of the electrode material.

[0050] Driving the agglomeration or mixing behavior of electrode particles: The second binder helps to form a dry film with high strength and high adhesion to the current collector during the dry mixing process.

[0051] Optimizing the peel strength between the electrode film and the current collector: During the hot pressing process of the composite current collector, the second binder can soften at a lower temperature and composite more tightly with the current collector, thereby optimizing the peel strength between the electrode film and the current collector.

[0052] Improving the cycle stability and electrochemical performance of the battery: Through the above-mentioned effects, the second binder helps to improve the cycle stability and electrochemical performance of the battery, thereby improving the safety of the battery.

[0053] Enhance the tensile strength and flexibility of the electrode film: Especially for active materials with a particle size of less than 5 microns, the addition of the second binder improves the electrochemical performance of the dry electrode, thereby improving the energy density and cycle stability of the battery.

[0054] Furthermore, the second binder includes at least one of PEG, PEO, amorphous PVDF, PMMA and polyvinyl chloride.

[0055] Specifically, the second binder includes at least one of PEG (polyethylene glycol), PEO (polyethylene oxide), amorphous PVDF (polyvinylidene fluoride), PMMA (polymethyl methacrylate) and polyvinyl chloride.

[0056] In the specific implementation process of the present invention, the above-mentioned binder not only has a lower melting point, better bonding effect, and better fit with PTFE, but also has good ion affinity and can form a strong interaction with lithium ions, thereby promoting the migration of lithium ions in the electrode material. This affinity helps to reduce the ion transfer impedance during the battery charging and discharging process and improve the power density and energy efficiency of the battery.

[0057] In addition, these binder materials also have certain flexibility and elasticity, which can maintain the integrity of the electrode membrane during the volume expansion and contraction during the battery charging and discharging process, reduce the structural damage of the electrode material caused by mechanical stress, and thus maintain the long-term stability and cycle life of the battery.

[0058] These secondary binders not only enhance the bonding properties of the electrode membrane, but also improve the electrochemical performance of the battery by improving the ion transport characteristics, making the battery perform well in terms of high efficiency, high stability and long life.

[0059] Furthermore, the mass ratio of the first binder to the second binder is 1:0.1-5.

[0060] Within this mass ratio range, on the one hand, the inactive material accounts for a small proportion in the entire active electrode system, which can improve the electrochemical performance of the battery; on the other hand, adjusting the amount of the second binder for different systems can effectively improve the film forming properties and mechanical strength of the membrane, providing a good foundation for the subsequent assembly of all-solid-state batteries.

[0061] Furthermore, the dry electrode membrane comprises, by weight, 30 to 95 parts of active material, 0 to 60 parts of solid electrolyte, 0.5 to 10 parts of conductive agent and 0.5 to 5 parts of binder.

[0062] Typically but not limiting, the composition of the dry electrode membrane can be calculated by weight, wherein the amount of active material can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts, or any value in the range of 30 to 95 parts; the amount of conductive agent can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, or any value in the range of 0.5 to 10 parts; the amount of binder can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 5 parts, or any value in the range of 0.5 to 5 parts.

[0063] The conductive agent includes at least one of VGCF, carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and graphene.

[0064] Furthermore, the active material includes a positive electrode active material and a negative electrode active material.

[0065] The positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel manganese cobalt oxide.

[0066] The negative electrode active material includes carbon material, silicon material, silicon-carbon composite material, lithium titanate or alloy material.

[0067] Furthermore, the active material is a positive electrode active material.

[0068] The dry-process positive electrode film comprises, by weight, 30 to 95 parts of positive electrode active material, 4 to 60 parts of solid electrolyte, 0.5 to 5 parts of conductive agent and 0.5 to 5 parts of binder.

[0069] Typically but not limiting, the composition of the dry cathode film can be calculated by weight, wherein the amount of the cathode active material can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts, or any value within the range of 30 to 95 parts; the amount of the solid electrolyte can be 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts , 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts or 60 parts, or it can be any value in the range of 4 to 60 parts; the number of conductive agents can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 5 parts, or it can be any value in the range of 0.5 to 5 parts; the number of binders can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 5 parts, or it can be any value in the range of 0.5 to 5 parts.

[0070] The solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte and a composite electrolyte.

[0071] The second aspect of the present invention provides a method for preparing the dry electrode membrane, wherein the active material, the conductive agent and the binder are evenly mixed at a mixing speed of 300rpm-20000rpm and a mixing time of 0.1h-5h, followed by fiberization and finally a film formation using a roller press to obtain the dry electrode membrane.

[0072] Furthermore, the mixing temperature is less than 19°C.

[0073] The fiberizing is performed using high speed high shear equipment.

[0074] The high speed high shearing device includes at least one of a jet mill, a twin screw extruder, a mixer and a differential speed roller press. The third aspect of the present invention provides a dry electrode, including a current collector and a dry electrode film disposed on at least one side of the current collector.

[0075] A fourth aspect of the present invention provides a battery, comprising the dry electrode described in the third aspect.

[0076] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0077] Example 1

[0078] This embodiment provides a dry-process positive electrode membrane, comprising 80 g of NCM, 2 g of VGCF, and Li 5.5 PS 4.5 Cl 1.5 18 g of PUFA and 1 g of amorphous PVDF are mixed, and then 1 g of PTFE is added, the mixture is mixed at a temperature below 19° C., and then fiberized under high speed and high shear force, and film-formed by a hot roller press to obtain the dry-process positive electrode membrane.

[0079] Example 2

[0080] This embodiment provides a dry-process positive electrode membrane, comprising 80 g of NCM, 2 g of VGCF, and Li 5.5 PS 4.5 Cl 1.5 18 g of PTFE and 1.5 g of amorphous PVDF are mixed, and then 2 g of PTFE is added, the temperature is controlled below 19° C., and the mixture is fiberized under high speed and high shear force, and a film is formed by a hot roller press to obtain the dry-process positive electrode membrane.

[0081] Example 3

[0082] This embodiment provides a dry-process positive electrode membrane, comprising 80 g of NCM, 2 g of VGCF, and Li 5.5 PS 4.5 Cl 1.5 18 g of PTFE and 2 g of amorphous PVDF are mixed, and then 2 g of PTFE is added, the temperature is controlled below 19° C., and the mixture is fiberized under high speed and high shear force, and a film is formed by a hot roller press to obtain the dry-process positive electrode membrane.

[0083] Example 4

[0084] This embodiment provides a dry-process positive electrode membrane. The difference from Embodiment 1 is that PEG is used to replace the amorphous PVDF in Embodiment 1. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described again.

[0085] Example 5

[0086] This embodiment provides a dry-process positive electrode membrane. The difference from Embodiment 1 is that PEO is used to replace the amorphous PVDF in Embodiment 1. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described again.

[0087] Example 6

[0088] This embodiment provides a dry-process positive electrode membrane. The difference from Embodiment 1 is that PMMA is used to replace the amorphous PVDF in Embodiment 1. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described again.

[0089] Example 7

[0090] This embodiment provides a dry-process positive electrode membrane. The difference from Embodiment 1 is that polyvinyl chloride is used to replace the amorphous PVDF in Embodiment 1. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described again.

[0091] Example 8

[0092] This embodiment provides a dry-process positive electrode membrane. The difference from Example 1 is that amorphous PVDF and PEG are used to replace the amorphous PVDF in Example 1, wherein the amount of amorphous PVDF is 0.5 g and the amount of PEG is 0.5 g. The other raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0093] Example 9

[0094] This embodiment provides a dry-process negative electrode membrane, which comprises mixing 95 g of micron silicon, 5 g of VGCF, and 1 g of amorphous PVDF, and then adding 2 g of PTFE, and mixing at a temperature below 19° C., and then fiberizing the mixture under high speed and high shear force, and forming the mixture into a film by a hot roller press to obtain the dry-process negative electrode membrane.

[0095] Example 10

[0096] This embodiment provides a dry-process negative electrode membrane. The difference from Example 9 is that amorphous PVDF and PEG are used to replace the amorphous PVDF in Example 1, wherein the amount of amorphous PVDF is 0.5 g and the amount of PEG is 0.5 g. The other raw materials and methods are the same as those in Example 9 and will not be repeated here.

[0097] Comparative Example 1

[0098] This comparative example provides a dry-process positive electrode membrane. The difference from Example 1 is that amorphous PVDF is not used, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0099] Comparative Example 2

[0100] This comparative example provides a dry-process negative electrode membrane. Unlike Example 9, amorphous PVDF is not used. The remaining raw materials and methods are the same as those in Example 9 and will not be described again.

[0101] Test Example 1

[0102] The dry electrode films obtained in the examples and comparative examples were tested for tensile strength and peel strength.

[0103] The tensile strength test was carried out in accordance with the provisions of GB13022-919.

[0104] The obtained data are shown in Table 1 below.

[0105] Table 1

[0106]

[0107] It can be seen from Table 1 that the tensile strength of the membrane with the addition of the second binder is greatly improved. These low-melting-point binders, especially amorphous PVDF, can improve the surface energy of materials of different particle sizes during the mixing process, promote the uniform dispersion of particles, and soften the wrapped particles under high shear force, making the particles more tightly bonded, thereby enhancing the tensile strength of the membrane.

[0108] Test Example 2

[0109] Figure 1 This is a photo of the dry-process negative electrode film obtained in Example 2. No second binder was added. Since the micron Si particles have a large specific surface area and poor film-forming properties, the membrane is very easy to crack.

[0110] Figure 2 This is a photograph of the dry-process negative electrode film obtained in Example 9. By adding the second binder, the film-forming property is greatly improved, and the mechanical strength of the film is also significantly improved.

[0111] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A dry electrode membrane for an all-solid-state battery, characterized in that: including active materials, conductive agents and binders; The binder includes a first binder and a second binder; the mass ratio of the first binder to the second binder is 1:0.1-5; The first binder is polytetrafluoroethylene or a copolymer of tetrafluoroethylene and a monomer; The melting point of the second binder is less than 120° C.; the second binder comprises at least one of PEG, PEO, PMMA and polyvinyl chloride; The preparation method of the dry electrode membrane for all-solid-state batteries is to mix the active material, the conductive agent and the binder evenly, the mixing speed is 300rpm-20000rpm, the mixing time is 0.1h-5h, and then fiberize, and finally use a roller press to form a film to obtain the dry electrode membrane.

2. The dry electrode film for all-solid-state battery according to claim 1, characterized in that: The invention comprises 30 to 95 parts of active material, 0 to 60 parts of solid electrolyte, 0.5 to 10 parts of conductive agent and 0.5 to 5 parts of binder in parts by weight; The conductive agent includes at least one of VGCF, carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and graphene.

3. The dry electrode film for all-solid-state battery according to claim 1, characterized in that: The active material includes a positive electrode active material and a negative electrode active material; The positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel manganese cobalt oxide; The negative electrode active material includes carbon material, silicon material, silicon-carbon composite material, lithium titanate or alloy material.

4. The dry-process electrode film for all-solid-state batteries according to claim 1, characterized in that: The active material is a positive electrode active material; The dry cathode film comprises 30-95 parts of cathode active material, 4-60 parts of solid electrolyte, 0.5-5 parts of conductive agent and 0.5-5 parts of binder in parts by weight; The solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte and a composite electrolyte.

5. The dry-process electrode film for all-solid-state batteries according to claim 1, characterized in that: The mixing temperature is less than 19°C; The fiberizing is performed using a high-speed high-shear device; The high-speed high-shearing equipment includes at least one of a jet mill, a twin-screw extruder, a mixer and a differential speed roller press.

6. A dry electrode for an all-solid-state battery, characterized in that: It comprises a current collector and a dry electrode film arranged on at least one side surface of the current collector; The dry electrode membrane is a dry electrode membrane for an all-solid-state battery as described in any one of claims 1 to 5.

7. An all-solid-state battery, characterized in that: Including the dry electrode for all-solid-state battery as described in claim 6.

Citation Information

Patent Citations

  • In-situ preparation method of dry-method electrode membrane and dry-method electrode thereof

    CN114171710A

  • Dry-method electrode film and preparation method thereof

    CN116705972A

  • Dry particle based electrochemical apparatus and methods of making same

    CN1838999A

  • Electrode and manufacturing method of electrode

    JP2020077614A